Acquired von Willebrand syndrome and lymphoproliferative disorders: A case report. Issue 5 (9th March 2020) - Nicol, Christophe; Raj, Leela; Guillerm, Gaëlle; Couturaud, Francis; Eveillard, Jean‐Richard; Pan‐Petesch, Brigitte
Abstract: Acquired von Willebrand syndrome is a rare bleeding disorder often secondary to an underlying lymphoproliferative disorder. We report a case in whom response of both the acquired von Willebrand syndrome and smoldering multiple myeloma persist 14 months after daratumumab treatment discontinuation. Abstract : Acquired von Willebrand syndrome is a rare bleeding disorder often secondary to an underlying lymphoproliferative disorder. We report a case in whom response of both the acquired von Willebrand syndrome and smoldering multiple myeloma persist 14 months after daratumumab treatment discontinuation.